2023
DOI: 10.1021/acscatal.3c00803
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Ensemble Effect on Dual-Pt atom-on-Rh Nanosheets Enables High-Efficiency and Anti-CO Alkaline Hydrogen Oxidation

Abstract: Explicit atomic coordinations of binary metal atoms on low-dimensional host–guest-type bimetallic nanomaterials can arouse unique ensemble effects and significantly improve the catalysis performances, but they confront a formidable challenge in chemical synthesis. Here, we draw on a thermoinduced secondary crystallization process of preprepared amorphous/crystalline hybrid ultrathin Rh nanosheets (NSs) to capture Pt atoms into the two-dimensional (2D) Rh lattice, by which precisely controlled Pt atomic dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In practical fuel cells, the presence of trace CO impurities in the industrial hydrogen supply can severely poison Pt-based anode HOR catalysts, which significantly reduces their lifetime. [45][46][47]…”
Section: Methodsmentioning
confidence: 99%
“…In practical fuel cells, the presence of trace CO impurities in the industrial hydrogen supply can severely poison Pt-based anode HOR catalysts, which significantly reduces their lifetime. [45][46][47]…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Xie et al reported the synthesis of amorphous/crystalline hybrid ultrathin Rh nanosheets (a/c-Rh NSs) with Pt atoms into the Rh lattice. [40] Interestingly, the Pt atomic dispersion can be precisely controlled from a single atom to dual atoms and further to clusters (Figure 4a). Among all the as-synthesized catalysts, the dual-Pt atom-on-Rh (Pt 2 -Rh) possesses the highest alkaline HOR activity due to its pairwise Pt 2 -on-Rh coordination feature that can induce a specific host-guest ensemble effect.…”
Section: Heyrovsky Stepmentioning
confidence: 99%
“…Zhang et al reported the synthesis of RhMo nanosheets (RhMo NSs) with metastable phase. [40] The RhMo NSs are actually a unique core/shell structure, of which the core is the metastable RhMo alloy in hexagonal close packed (HCP) phase and the shell is the stable RhMo alloy in FCC phase. RhMo NSs possess a significant large surface area due to the atomic thickness, which can provide abundant active sites.…”
Section: Heyrovsky Stepmentioning
confidence: 99%
“…Alkaline exchange membrane fuel cells (AEMFCs) are regarded as next-generation technology for hydrogen-to-electric energy conversion. 1–3 One of the most important advantages is that the electrocatalysts for the cathodic oxygen reduction reaction could get rid of the dependence on platinum group metals (PGMs) compared to the proton exchange membrane-based counterpart operated under harsh acidic conditions. 4–6 Nevertheless, the anodic hydrogen oxidation reaction (HOR) in high pH electrolytes suffers from more complex catalytic mechanisms and thus sluggish kinetics.…”
Section: Introductionmentioning
confidence: 99%